2017
DOI: 10.1080/00986445.2017.1330746
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Machine Vision Based Image Analysis Method for the Analysis of Mixing Elements in Rotary Drums

Abstract: Mixing performance in continuous rotary drums has been studied. The video analysis method was developed to evaluate different configurations of straight lifters in the rotary drum. The method converts a captured video into a single image, called stack image. The color marker tracking was estimated based on the color saturation of the stack image. Coefficients of variation and mixing indices were calculated from the color saturation profiles for different straight blade lifter configurations. The video analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The relationship between pH and hydrogen ion concentration is as shown in Equation (40). Koiranen [81] used HNO 3 solution as the tracer, and found that the acid tracer could lead to deviation between repetitive experiments. The experimental results based on acid tracer indicated no clear trends in the mixing at high viscous media when the mixing conditions were changed.…”
Section: Measuring Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between pH and hydrogen ion concentration is as shown in Equation (40). Koiranen [81] used HNO 3 solution as the tracer, and found that the acid tracer could lead to deviation between repetitive experiments. The experimental results based on acid tracer indicated no clear trends in the mixing at high viscous media when the mixing conditions were changed.…”
Section: Measuring Technologymentioning
confidence: 99%
“…[17][18][19][20]43] In order to find a more accurate method, the digital image processing began to be applied in chemical engineering for RTD curves in recent years. [81][82][83] Nigam et al [84] first developed the measurement of RTD curve by digital image processing in the tundish water model. The experimental procedure is shown in Figure 18.…”
Section: Measuring Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy of results obtained from proposed method has been validated against results of conventional RTD methods. For carrying out RTD analysis in tundish, the present work utilizes the wellestablished concepts of digital image processing having applications in different fields of research [18][19][20][21][22]. A novel velocity threshold-based Lucas-Kanade (VT-LK) method for measuring the residence time of incoming fluid in steelmaking tundish has been developed.…”
Section: Introductionmentioning
confidence: 99%